2013
DOI: 10.1159/000349943
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic Pruritus: Relief of Itching by Gabapentin and Pregabalin

Abstract: Background: Pruritus (skin irritation or itching) is common in patients with chronic kidney disease (CKD) stages 4 and 5. It is associated with disrupted sleep, reduced quality of life, depression and increased mortality. A video of a patient describing the symptoms is at vimeo.com/49458473. Methods: We used gabapentin or pregabalin in 71 consecutive patients, 82% male. 25 had CKD stage 4 or 5, median eGFR = 17, range 9-30; 40 were on haemodialysis; 6 on peritoneal dialysis. Median itch severity score out of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 11 publications
5
82
2
2
Order By: Relevance
“…Furthermore, an association between these measures and pruritus is no longer observed in the 2012-2015 data, a finding supported by other recent studies (11,20,24). There is no published interventional study showing that lowering serum phosphorus improves pruritus.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Furthermore, an association between these measures and pruritus is no longer observed in the 2012-2015 data, a finding supported by other recent studies (11,20,24). There is no published interventional study showing that lowering serum phosphorus improves pruritus.…”
Section: Discussionmentioning
confidence: 75%
“…Another uncontrolled trial of ketotifen showed no effect on pruritus, and uncontrolled trials of hydroxyzine and chlorphenamine showed a partial effect or no effect (32). Plasma histamine levels are not associated with the severity of pruritus (33), and patients frequently report that antihistamines are ineffective (11,21,34). It has been suggested that antihistamines should be tried first, because they are unlikely to be harmful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregabalin alleviated pruritus in 81% of the patients after a median time of 2.5 months (the median severity of itch reduced from 8 to 2). Over sedation was the sole reported adverse effect of pregabalin which occurred in 2 patients (30 Results of a 4 week study designed by Foroutan et al showed that pregabalin (50 mg after each dialysis session) was more effective than doxepin (10 mg/day) in reducing the severity of UP, evaluated by the VAS and 5-D itch scale, and improving quality of life, evaluated by the 5-D itch scale and dermatology life quality index, in a group of hemodialysis patients (N= 72). They also noted that the most antipruritic effects of pregabalin appeared at the end of the first week of the study, and the effects continued through the remained course of the trial.…”
Section: Antipruritic Effects Of Pregabalin On Uremic Pruritusmentioning
confidence: 99%
“…97 Pregabalin, a medication similar to gabapentin, may also improve CKD-aP 37,99 and may be particularly useful when patients are not able to tolerate gabapentin. 1,100 In a randomized, crossover trial, 50 HD patients were assigned to gabapentin 300 mg or pregabalin 75 mg daily. After a 6-week treatment period, both the medications significantly improved pruritus intensity.…”
mentioning
confidence: 99%